2017
DOI: 10.1097/md.0000000000006426
|View full text |Cite
|
Sign up to set email alerts
|

Green tea and the risk of prostate cancer

Abstract: Prostate cancer (PCa) now remains the 2nd most frequently diagnosed cancer. In recent years, chemoprevention for PCa becomes a possible concept. Especially, many phytochemicals rich foods are suggested to lower the risk of cancer. Among these foods, green tea is considered as effective prevention for various cancers. However, clinical trials and previous meta-analyses on the relationship between green tea consumption and the risk of PCa have produced inconsistent outcomes. This study aims to determine the dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(33 citation statements)
references
References 42 publications
0
30
0
3
Order By: Relevance
“…There was no obvious significant association of high consumption of tea with breast cancer, non‐melanoma skin cancer, bladder cancer, prostate cancer, pancreatic cancer, colorectal cancer, renal cell cancer, laryngeal cancer, and pharyngeal cancer . Consistent results were obtained for bladder cancer, laryngeal cancer, liver cancer, pancreatic cancer, and oral cancer checking the concordance, direction, and significance of the meta‐analyses of the same exposure and cancer outcome.…”
Section: Resultsmentioning
confidence: 91%
“…There was no obvious significant association of high consumption of tea with breast cancer, non‐melanoma skin cancer, bladder cancer, prostate cancer, pancreatic cancer, colorectal cancer, renal cell cancer, laryngeal cancer, and pharyngeal cancer . Consistent results were obtained for bladder cancer, laryngeal cancer, liver cancer, pancreatic cancer, and oral cancer checking the concordance, direction, and significance of the meta‐analyses of the same exposure and cancer outcome.…”
Section: Resultsmentioning
confidence: 91%
“…Previous studies have shown that it can prevent both dental caries and periodontal disease [10][11][12]. In addition to its beneficial effects on various health outcomes, such as all-cause mortality, cardiovascular disease, cancers, non-alcoholic fatty liver disease, metabolic syndrome, diabetes, and other health outcomes [13][14][15][16][17][18][19][20], green tea consumption is also considered to have an effect on oral health. In spite of abundant benefits from the basic sciences, there are relatively fewer clinical studies on the merit of green tea on oral health [21].…”
Section: Introductionmentioning
confidence: 99%
“…Besides, flavonoid fraction extracted from natural compounds displayed substantial radioprotective effect against destruction, which is stimulated by γ-irradiation in mice (Bratkov, Shkondrov, Zdraveva, & Krasteva, 2016). Intriguingly, powerful evidence from both epidemiological and laboratory studies demonstrate that dietary intake of flavonoids is able to reduce the risk of varied cancers progression, such as prostate, breast, thyroid, lung, and ovarian cancers (Ahmed, Abd El-Hafeez, Abbas, Abdelhamid, & Abdel-Aziz, 2018; Ci, Qiao, & Han, 2016;Estevez-Sarmiento et al, 2018;Goncalves, de Freitas, & Ferreira, 2017;Guo et al, 2017; X. Xiao et al, 2018).…”
Section: Introductionmentioning
confidence: 99%